Rëâdīńg wõrdš wîth ōrńåmêńtš: is there a cost? - Duñabeitia, Jon Andoni; Perea, Manuel; Labusch, Melanie (Frontiers in Psychology, 2023)
Recent research has reported that adding a non-existent diacritical mark to a word only produces a small reading cost compared to the intact word. Here we examined whether this minimal reading cost is due to: (1) the resilience of letter detectors to the perceptual noise (i.e., the cost should be small and comparable for words and nonwords) or (2) top-down lexical processes that normalize the percept for words (i.e., the cost would be larger for nonwords). To that end, we designed a letter detection experiment in which a target stimulus (either a word or a nonword) was presented intact or with extra non-existent diacritics (e.g., amigo [friend] vs. ãmîgô; agimo vs. ãgîmô). We found faster and more accurate responses when the target letter occurred in a word than in a nonword (i.e., a word superiority effect). Notably, there was only a minimal advantage of the intact stimuli over the stimuli with superfluous diacritics, restricted to the error rates, that was similar for words and nonwords. Therefore, the arrays of letter detectors in the word recognition system appear to be resilient to the presence of non-existent diacritics in the visual input without the need for feedback from higher levels of processing.